Boosting Trust and Purchase Enthusiasm: Impact of Online Customer Ratings and E-Service Quality in Online Food Delivery - Putri Enjelika; Astri Ayu Purwati; Jusmarni Jusmarni (Yayasan Pendidikan Islam Al-Matani, 2023)
This study aims to determine the effect of online customer ratings and e-service quality on e-trust and purchase intention in food delivery on gofood in Pekanbaru. The population and sample used in this research is by using accidental sampling method selected based on determining the sample by taking respondents who happen to be available or available somewhere according to the research context. Thus, the number of samples in this study were 200 respondents. The method of analysis in this study is Stuctural Equation Modeling (SEM) using SmartPLS 4 software. The research results obtained by online customer ratings and e-service quality have a positive and significant effect on e-trust, online customer ratings have a positive significant effect on purchase intention and e-trust has a positive significant effect on purchase intention while e-service quality has a positive and insignificant effect on purchase intention. Thus the better online customer rating and e-service quality carried out by gofood will have an impact on increasing consumer e- trust and buying interest.